A simple and sensitive method for determination of Norfloxacin in pharmaceutical preparations (Brazilian Journal of Pharmaceutical Sciences, 2015)
;In this approach, a new voltammetric method for determination of norfloxacin was proposed with high sensitivity and wider detection linear range. The used voltammetric sensor was fabricated simply by coating a layer of graphene oxide (GO) and Nafion composited film on glassy carbon electrode. The advantage of proposed method was sensitive electrochemical response for norfloxacin, which was attributed to the excellent electrical conductivity of GO and the accumulating function of Nafion under optimum experimental conditions, the present method revealed a good linear response for determination of norfloxacin in the range of 1×10;-8;mol/L-7×10;-6; mol/L with a detection limit of 5×10;-9; mol/L. The proposed method was successfully applied in the determination of norfloxacin in capsules with satisfactory results.;